Just like a Woman? New Comparative Evidence on the Gender Income Gap across Eastern Europe and Central Asia - Niels-Hugo Blunch (Institute of Labor Economics (IZA), 2018)
I examine the incidence and determinants of the gender income gap in Kazakhstan, Macedonia, Moldova, Serbia, Tajikistan, and Ukraine using recent household data based on an identical survey instrument across countries. Four main results are established, using a range of estimators, including OLS, interval regression, and quantile regression: (1) the presence of a substantively large gender income gap (favoring males) in all six countries; (2) some evidence of a gender-related glass ceiling in some of these countries; (3) some evidence that endowments diminish the income gaps, while the returns to characteristics increase the gaps; and (4) while observed individual characteristics explain part of the gaps, a substantial part of the income gap is left unexplained. In sum, these results are consistent with the presence of income discrimination towards females but at the same time also point towards the importance of continued attention towards institutions and economic policy for decreasing the gender income gap in these former formally gender neutral economies—notably through attention towards the maternity and paternity leave system, as well as public provision of child care.
Keywords: J16; J31; J7; 330; gender; income gap; Oaxaca-Blinder decomposition; detailed decomposition; maternity/paternity leave policies; Eastern Europe and Central Asia